IKK-mediated CYLD phosphorylation and cellular redox activity - Adnan Erol (BMC, 2022)
Abstract Oxidative stress is important in the development of obesity-related nephropathy (ORN). A causal relationship between IKK and ORN via CYLD-mediated inhibition of NRF2 has been described. However, contradictory explanations about the functioning of the mechanisms that will be effective in the pathogenesis require clarification.